EVALUASI TEMUAN AUDIT OPERASIONAL DAN IMPLIKASINYA TERHADAP PENGAMBILAN KEPUTUSAN MANAJERIAL (STUDI KASUS PADA HISANA FRIED CHICKEN CABANG ABU BAKAR) - Latifa , Latifa; Qiqi Zakiyah Ainiyah (Juremi: Jurnal Riset Ekonomi, 2025)
This study was conducted with the aim of evaluating operational audit findings and analyzing their effect on managerial decision making at Hisana Fried Chicken Abu Bakar Jember Branch. Operational audit is an important tool that can be used to ensure efficiency, suitability of procedures, and as a basis for managerial decision making in the face of intense competition in the fast food industry today. This research uses a qualitative approach with a case study method and the data collection techniques chosen are through interviews and documentation of audit results. The resulting research shows that operational audits have an important role in identifying operational weaknesses, including aspects of cleanliness, cash recording, and service quality. Management uses audit findings as a reference in decision-making. The main challenge faced in implementing audit recommendations is the characteristics of human resources. However, management showed a high level of commitment in following up on audit findings to maintain operational quality. This study provides recommendations for increasing the frequency of audits and strengthening the audit function as a coaching and capacity building tool for human resources.